New approaches in W gravities - Abreu, E. M.C. [UNESP]; De Souza Dutra, A. [UNESP]; Wotzasek, C. [UNESP] (American Physical Society (APS), 2002)
We devote effort to studying some nonlinear actions, characteristic of W theories, in the framework of the soldering formalism. We disclose interesting new results concerning the embedding of the original chiral W particles in different .metrical spaces in the final soldered action; i.e., the metric is modified by the soldering interference process. The results are presented in a weak field approximation for the WN case when N≥3 and also in an exact way for W2. We promote a generalization of the interference phenomenon to WN theories of different chiralities and show that the geometrical features introduced can yield a new understanding of the interference formalism in quantum field theories. © 2002 The American Physical Society.